ANALYSIS OF SCIENCE LITERATURE ABILITY OF BIOLOGY EDUCATION STUDENTS IN PLANT PHYSIOLOGY COURSE - N Nadya; Uswatun Hasanah; Muhammad Akram; Martina Asiati Napitupulu (Jurnal Pelita Pendidikan, 2022)
Prospective teachers are required to have adequate scientific literacy skills to support the achievement of the National SDGs 2030 goals. Research is needed that aims to analyze the level of scientific literacy skills of students of the 2018 Biology Education Study Program, Medan State University in the Plant Physiology course which was held at UNIMED in May-July 2021. This study uses a mixed descriptive method with a sequential explanatory strategy. The sample in this study amounted to 76 students who were determined through a random sampling technique. The data in this study were collected through a closed questionnaire and an observation sheet for the KKNI Plant Physiology assignment. This study uses descriptive statistical analysis techniques for quantitative data, questionnaires, and interactive analysis for qualitative data, the KKNI's task observation includes three activity lines, namely data reduction, data presentation, and conclusion drawing. The results obtained through questionnaires showed that the scientific literacy skills of Biology education students at the State University of Medan in the Plant Physiology course were in the high category with a percentage of 63.72%. Meanwhile, the scientific literacy ability of Biology education students at the State University of Medan based on the task analysis of the KKNI for the Plant Physiology course is in the low category with a percentage of 55.69%.